Isolation and characterization of major histocompatibility complex class IIB genes from the nurse shark. - Bartl, S (1994)
The major histocompatibility complex (MHC) contains a set of linked genes which encode cell surface proteins involved in the binding of small peptide antigens for their subsequent recognition by T lymphocytes. MHC proteins share structural features and the presence and location of polymorphic residues which play a role in the binding of antigens. In order to compare the structure of these molecules and gain insights into their evolution, we have isolated two MHC class IIB genes from the nurse shark, Ginglymostoma cirratum. Two clones, most probably alleles, encode proteins which differ by 13 amino acids located in the putative antigen-binding cleft. The protein structure and the location of polymorphic residues are similar to their mammalian counterparts. Although these genes appear to encode a typical MHC protein, no T-cell-mediated responses have been demonstrated in cartilaginous fish. The nurse shark represents the most phylogenetically primitive organism in which both class IIA [Kasahara, M., Vazquez, M., Sato, K., McKinney, E.C. & Flajnik, M.F. (1992) Proc. Natl. Acad. Sci USA 89, 6688-6692] and class IIB genes, presumably encoding the alpha/beta heterodimer, have been isolated.